Can a Software-Based Metronome Tool Enhance Compression Rate in a Realistic 911 Call Scenario Without Adversely Impacting Compression Depth for Dispatcher-Assisted CPR?. Issue 4 (23rd July 2018) - Scott, Greg; Barron, Tracey; Gardett, Isabel; Broadbent, Meghan; Downs, Holly; Devey, Leslie; Hinterman, EJ; Clawson, Jeff; Olola, Christopher
Abstract: Introduction: Implementation of high-quality, dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) is critical to improving survival from out-of-hospital cardiac arrest (OHCA). However, despite some studies demonstrating the use of a metronome in a stand-alone setting, no research has yet demonstrated the effectiveness of a metronome tool in improving DA-CPR in the context of a realistic 911 call or using instructions that have been tested in real-world emergency calls. Hypothesis: Use of the metronome tool will increase the proportion of callers able to perform CPR within the target rate without affecting depth. Methods: The prospective, randomized, controlled study involved simulated 911 cardiac arrest calls made by layperson-callers and handled by certified emergency medical dispatchers (EMDs) at four locations in Salt Lake City, Utah USA. Participants were randomized into two groups. In the experimental group, layperson-callers received CPR pre-arrival instructions with metronome assistance. In the control group, layperson-callers received only pre-arrival instructions. The primary outcome measures were correct compression rate (counts per minute [cpm]) and depth (mm). Results: A total of 148 layperson-callers (57.4% assigned to experimental group) participated in the study. There was a statistically significant association between the number of participants who achieved the target compression rate and experimental study group (P=.003), and the experimental group had a significantly higher median compression rate than the control group (100 cpm and 89 cpm, respectively; P=.013). Overall, there was no significant correlation between compression rate and depth. Conclusion: An automated software metronome tool is effective in getting layperson-callers to achieve the target compression rate and compression depth in a realistic DA-CPR scenario. Scott G, Barron T, Gardett I, Broadbent M, Downs H, Devey L, Hinterman EJ, Clawson J, Olola C. Can a software-based metronome tool enhance compression rate in a realistic 911 call scenario without adversely impacting compression depth for dispatcher-assisted CPR? Prehosp Disaster Med. 2018;33(4):399–405